Kritik al-qur'an terhadap krisis ekologi: studi analisis makna al-fasad fi al-barr wa al-bahr dalam tafsir ibnu katsir dalam konteks banjir sumatera-aceh - aziz, rifqi zulfani (Maliki Interdisciplinary Journal, 2026)
The escalating global ecological crisis necessitates a re-examination of its root causes from a theological perspective. This study aims to analyze the Qur'anic critique of environmental destruction through the examination of the terminology "al-fasad fi al-barr wa al-bahr" (mischief on land and sea) in the Tafsir of Ibn Kathir, contextualized within the flash flood tragedy in Aceh and Sumatra in late 2025. The research employs a qualitative descriptive method with a library research approach, integrating classical exegesis literature, contemporary ecological journals, and factual data from recent disaster reports. The findings indicate that the flash flood phenomenon in Aceh was not merely a climatic anomaly, but a direct consequence of "ecological disobedience" in the form of illegal logging. In his exegesis, Ibn Kathir emphasizes that every form of corruption (fasad) on land and at sea is a moral consequence of human behavior that betrays the mandate as a "khalifah" (steward). The disaster serves as a manifestation of the withdrawal of nature's blessings due to the disregard for the cosmic balance (mizan). This study concludes that resolving the ecological crisis requires an "ecological repentance" through strict law enforcement against environmental violators and the revitalization of nature management ethics based on monotheistic (Tawhid) values to ensure the sustainability of future generations.